POLITICAL-ECONOMIC CHINA IN SOUTHEAST ASIA AND BETWEN IMPACT ON THE INDONESIAAN ECONOMY - Rohman, Syaiful; Napang, Marthen (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2022)
China's economy has made this country one of the world's economic powerhouses. China under the leadership of President Xi Jinping has implemented various strategic policies in building China connections. Massive investment and economic expansion made throughout the world make China increasingly have a great influence in the global world. In Southeast Asia, especially Indonesia and Malaysia, cooperation with China in the manufacturing, export-import, and finance sectors has existed for a long time and has become an important economic route in Southeast Asia. These three countries are the key to the Southeast Asian economy with a large population and strong purchasing power. This study analyzes the political economy relationship between Indonesia and southeast Asia with China using qualitative methods, and descriptive analysis based on credible data. The results of this study indicate that in the last ten years the economic relations between Indonesia and southeast Asia with China under the leadership of President Xi Jinping have continued to experience significant improvements in various sectors, especially in the fields of finance and infrastructure.